Food for schooling in Bangladesh - International Food Policy Research Institute (International Food Policy Research Institute, 2001)
Bangladesh has led the world in creating innovative development programs that can be replicated successfully in other developing countries. The renowned Grameen Bank, which lends small sums to poor women to start up their own businesses, is a notable example. Bangladesh has also implemented the first-ever Food for Schooling program, which may soon be added to the list of successful antipoverty interventions.